Exploring Self-Leadership as a Predictor of Student Engagement in Religious Internship Programs - Moh. Muslim; Shofiatul Jannah; Imroatun Imroatun (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study investigates the influence of self-leadership on student engagement among students at Madrasah Aliyah Ma’arif NU in Kota Blitar, a context where fostering independent learning is crucial for academic and personal development. Employing a quantitative approach with Spearman's Rank Correlation, the research involved 126 students selected through proportional random sampling. Data were collected using a validated questionnaire and analyzed with IBM SPSS 24.0. Prerequisite tests indicated that the data, while not normally distributed, met the linearity assumption. The results demonstrated a moderate positive correlation between self-leadership and student engagement (R = 0.436), with self-leadership accounting for 19% of the variance in engagement (R² = 0.190). The regression model was significant (p < 0.05), with the equation Y = 28.652 + 0.262X indicating a positive relationship between self-leadership and engagement. These findings underscore the significant role of self-leadership in promoting active participation, motivation, and commitment among students. While self-leadership is a key contributor, other factors also substantially influence engagement. The practical implications suggest that educators and policymakers at Islamic schools should prioritize developing students' self-leadership through strategies like reflective practices, granting autonomy, and providing targeted training. Future research should examine additional influencing variables and employ longitudinal designs to achieve a more comprehensive understanding.